Removal of Heavy Metal from Synthetic WastewaterUsing Calcined Golden Apple Snail Shells - Ketwong, Chatyapha; Trisupakitti, Somsuk; Nausri, Chompoo; Senajuk, Watchara (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 4 (2018): October-December 2018, 2018)
Westudied the removal of heavy metals from synthetic waste water samples by using Golden Apple Snail shells,calcined at 1050 O C: they were able to removeup to 30% of copper(II) ions, 88% of cadmium(II) ions and 56% of lead(II) ions. The best performance was at pH 6. Metal removal followed a stable pseudo-second order reaction equation with parameters, k 2 and q e , with k 2 values for Cu 2+ 0.00377, Cd 2+ 0.00278 and Pb 2+ 0.00365 g/mg-min and q e values of  9.65,25.9, 16.8 mg/g and we concluded that the sorption mechanism is primarily absorption into the pores of the sorbent . This adsorbing material had two advantages, that is, lower volume of the Golden Apple Snail Shell and a cost-effective absorbent. If further developed, this could lead to better and effective low cost treatment for polluted waste waters. Keywords: Golden Apple Snail Shell, Absorption, Cadmium, Copper, Lead, Sorption kinetics